The Future of Agriculture in Indonesia: Facing Climate Change and Globalization - Kurnianto, Bambang Tri (West Science Agro, 2024)
Agriculture is a vital sector in Indonesia, providing livelihoods for millions and contributing significantly to the national economy. However, the future of agriculture in the country is increasingly threatened by climate change and globalization. This article examines the challenges faced by Indonesian agriculture, including shifting weather patterns, water scarcity, and the pressures of global markets. It explores the potential impacts of these factors on food security, rural livelihoods, and environmental sustainability. The article also highlights innovative practices and policies that can help Indonesian farmers adapt to changing conditions, such as sustainable farming techniques, agroecology, and the use of technology. By analyzing case studies and existing literature, this study aims to provide insights into how Indonesia can navigate these challenges while promoting resilience and sustainability in its agricultural sector. Ultimately, the findings underscore the need for a collaborative approach involving farmers, policymakers, and the private sector to secure a sustainable agricultural future in Indonesia.